The Endovascular Sealing Device in Combination with Parallel Grafts for Treatment of Juxta/Suprarenal Abdominal Aortic Aneurysms: Short-term Results of a Novel Alternative. Issue 4 (October 2016) - De Bruin, J.L.; Brownrigg, J.R.; Patterson, B.O.; Karthikesalingam, A.; Holt, P.J.; Hinchliffe, R.J.; Loftus, I.M.; Thompson, M.M.
Abstract : Background: The chimney technique using parallel grafts offers an alternative to fenestrated or branched endovascular solutions for juxtarenal and suprarenal aneurysms. Endograft deployment proximal to the renal or visceral ostia is combined with parallel stents to the aortic side branches. Application of the chimney technique using the Nellix device (Ch-EVAS) may offer some potential advantages with respect to the seal between the endograft and the parallel grafts. This study aimed to investigate the feasibility and efficacy of the Nellix endovascular aneurysm sealing (EVAS) system in conjunction with parallel grafts for the treatment of juxtarenal and suprarenal aneurysms. Methods: A prospective evaluation of patients treated for juxtarenal and suprarenal non-ruptured aortic aneurysms using Ch-EVAS was undertaken in a single vascular unit. Patients were treated with this technique if they were unsuitable for either open repair or a custom-made complex branched/fenestrated endograft. Procedural, postoperative morbidity, and mortality data were recorded. Results: Between March 2013 and April 2015, 28 patients were treated with Ch-EVAS. The median age was 75 years (range 60–87 years) and the median aneurysm diameter 66 mm (IQR 60–73 mm). Eight patients underwent suprarenal aneurysm repair including parallel grafts in the superior mesenteric artery and renal arteries. Five patients had a double chimney configuration; all the other patients were treated with a single chimney configuration. There was one 30-day or in-hospital mortality in a patient with a symptomatic aneurysm (4%) and three further deaths within 1 year of follow-up. One proximal type I endoleak and one type II endoleak occurred. Four patients underwent a reintervention. One patient experienced a transient ischemic attack and two patients suffered from a minor stroke (7%), therefore the total number of cerebrovascular complications was 11%. No patient required postoperative renal replacement therapy. Conclusions: Ch-EVAS appears to offer a feasible solution for juxtarenal and suprarenal aneurysms with adverse morphology. In this short-term follow-up endoleak rates were low and re-intervention rates were acceptable. Outcomes over extended follow-up will determine the application of this novel technique and better define which patients and aneurysm morphology can be treated effectively.